4f-23=57

Simple and best practice solution for 4f-23=57 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4f-23=57 equation:


Simplifying
4f + -23 = 57

Reorder the terms:
-23 + 4f = 57

Solving
-23 + 4f = 57

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '23' to each side of the equation.
-23 + 23 + 4f = 57 + 23

Combine like terms: -23 + 23 = 0
0 + 4f = 57 + 23
4f = 57 + 23

Combine like terms: 57 + 23 = 80
4f = 80

Divide each side by '4'.
f = 20

Simplifying
f = 20

See similar equations:

| -6x-5+3x=-32 | | -192+3x=108+15x | | a^2+b^2+2a+2b-3=0 | | 24x-12=24x+12 | | 2q-8=26 | | -3+3(-6x-3)+15x=6(x-8) | | 100x+2.75=221.00 | | -13x-152=-347 | | X-7.6=-4.9 | | 5x+4(18)=122 | | 5(4-X)+2(6+X)= | | x-6y=-7 | | 2v^2+5v-12=v^2+16 | | x=-10+6y | | 4(-2x-3)=52 | | 25b-13b-5=50b+17 | | 175x+2.75=274.00 | | -10=6+4v | | 3/5(5/6)-1/2=x | | 12+x=-2x+9 | | -10x-57+7x=30 | | x-24=-3x+8 | | 3x-76-12x=41 | | 2(3+4x)-3=19 | | -10x-11=-20x+9 | | -5=0.25(4+20a)-8a | | -7+5x=23+10x | | -6(x+3)-2x=3-(2x+5) | | 7x+76=-50 | | 6.7-x=4.9 | | N+5N=246 | | 3x-23=-4x-9 |

Equations solver categories